The role of services in global value chains: Assessing the servicification of Philippine manufacturing industries - Neil Irwin S. Moreno (Philippine Institute for Development Studies (PIDS), 2024)
The emergence of global value chains (GVCs) in recent years has underlined the increasing reliance of manufacturing industries on services. Manufacturing firms have intensively used service inputs, performed in-house services activities, and sold services embedded in, or bundled with goods. Considered a services economy, the Philippines could leverage services to develop a competitive manufacturing sector and strengthen its GVC integration. This study assessed the servicification of the Philippine manufacturing sector, in the context of trade and GVCs. Using trade in value added data, we observed that the contribution of services in Philippine manufacturing exports has been on par with that of its regional neighbors; however, Philippine manufacturing has had weak linkages with modern services, such as ICT and business services. Based on establishment surveys/censuses, Philippine manufacturing firms extensively use service inputs, but R&D activities and sale of services have been less common. We also estimated the relationship between servicification and export participation, and found that sale of industrial services, utilization of transport services, and employing R&D personnel were associated with higher probability of exporting. Drawing from the empirical findings, we posit the need to develop the country's modern services sectors, and strengthen their linkages with manufacturing industries. Promoting R&D and innovation among firms could also develop their capabilities, making them competitive to enter export markets. Moreover, firms looking to export could benefit from potential reductions in transport and logistics costs, brought about by the streamlining of transport regulations and procedures.
Keywords: 330; servicification; trade in value added; manufacturing; GVCs